2010
DOI: 10.1007/s11240-010-9735-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of unfertilized ovules in carrot (Daucus carota L.)

Abstract: To induce development of isolated carrot ovules, flowers were pollinated with pollen from different species. Effects of pollen origin, medium composition, and light conditions were evaluated for 13 carrot cultivars. The highest efficiency of development was recorded following pollination of carrot flowers with parsley pollen. The highest frequency of embryo formation (0.84%) was obtained for cv. 'Flamanka'; whereas the highest frequency of callus formation (1.56%) was obtained for cv. 'Karlena'. Medium supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…In cucumber, TDZ is successfully used for gynogenic induction and regeneration of embryos (Gémes-Juhász et al 2002;Diao et al 2009). Kielkowska and Adamus (2010) reported that medium supplement with indole-3-acetic acid (IAA) promoted embryo development (0.63%), while supplementation with 2,4-D (2,4-Dichlorophenoxyacetic acid) and 6-BA promoted callus development (1.34%) in culture of carrot unfertilized ovule. Addition of polyamine (spermidine and putrescine) in induction and regeneration media resulted in improved gynogenic embryos and haploid plantlets (Martínez et al 2000;Ebrahimi and Zamani 2009).…”
Section: Culture Mediummentioning
confidence: 99%
“…In cucumber, TDZ is successfully used for gynogenic induction and regeneration of embryos (Gémes-Juhász et al 2002;Diao et al 2009). Kielkowska and Adamus (2010) reported that medium supplement with indole-3-acetic acid (IAA) promoted embryo development (0.63%), while supplementation with 2,4-D (2,4-Dichlorophenoxyacetic acid) and 6-BA promoted callus development (1.34%) in culture of carrot unfertilized ovule. Addition of polyamine (spermidine and putrescine) in induction and regeneration media resulted in improved gynogenic embryos and haploid plantlets (Martínez et al 2000;Ebrahimi and Zamani 2009).…”
Section: Culture Mediummentioning
confidence: 99%
“…It was first envisioned as a technique to accelerate the breeding process and to use for practical and basic research in many crops (Dunwell 2010;Ferrie and Caswell 2010;Germanà 2011). While efficient protocols for microspore embryogenesis induction have been developed to obtain haploid and DH plants in several crops (Maluszynski et al 2003;Dunwell 2010;Ferrie and Caswell 2010), limited progress has been reported using anther cultures (Dohya et al 1997;Tyukavin et al 1999;Adamus and Michalik 2003;Górecka et al 2005;Smýka-lová et al 2009;), isolated microspore cultures (IMC; Dohya et al 1997;Górecka et al 2010;, or unfertilized ovule cultures (Kiełkowska and Adamus 2010) of Apiaceae species.…”
Section: Introductionmentioning
confidence: 99%
“…Ovules were isolated from enlarged ovaries under sterile conditions and placed in 60-mm Petri dishes containing 5 ml medium. Explants were cultured on one of the following media: H — according to Kiełkowska and Adamus ( 2010 ) with 0.06 μM indole-3-acetic acid (IAA); O — 1/2-strength Murashige and Skoog (MS) (Murashige and Skoog 1962 ) with 100 mM MnSO 4 , 4.16 mM Edamin K (Sigma Aldrich Ltd., Poznań, Poland),) and 30 g l −1 sucrose; SHI — full-strength MS with B5 vitamins (Gamborg et al 1968 ) and 0.57 μM IAA, 1.44 μM gibberellic acid (GA 3 ), 4.6 μM kinetin, and 40 g l −1 sucrose; SHT — SHI medium with 9.08 μM thidiazuron (TDZ); HT — H medium with 9.08 μM TDZ; HP — H medium with 1 mM putrescine; or SHP — SHI medium with 1 mM putrescine. All media contained 7 g l −1 Lab-agar (Biocorp, Warszawa, Poland) and were adjusted to pH 5.8 before autoclaving.…”
Section: Methodsmentioning
confidence: 99%
“…The ploidy level of regenerants was determined by flow cytometry as described by Kiełkowska and Adamus ( 2010 ). All diploid plants were then screened for PGI isozyme variants and DNA polymorphism at chs2 and ipi3 loci according to the protocols used for evaluation of the ovule donor plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation